Assessment of Current Capacity of Local Service Providers in Offshore Decommissioning Waste Management in Malaysia - Noordin, Nurin Adlina (Universiti Teknologi PETRONAS, 2013)
This project in its present form is to assess the current capacities of local service provider in offshore decommissioning waste management. The initial idea of limited studies on offshore decommissioning in Malaysia so as the increasing number of platform to be decommissioned has led to the justification of the project relevancy. The project is given more attention on waste management of established local service provider. The element will be studied start from the service provider current capacities, level of awareness and their potential capabilities in handling waste management. A single case study approach is applied on three different parties that involve in decommissioning waste management namely Fabrication Yard, Recycler and Hazardous Waste Disposal Service. Their capabilities in handling waste produced and their level of awareness will be evaluated. Hence, the controversial issued whether Malaysia have the availability and capacity of local service provider required for platform decommissioning waste management can be addressed.